Value Relevance and Users Confidence in Post International Financial Reporting Standards Adoption Era of Nigerian Banks - M.O., Oladejo; R.A., Adedokun (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
Conclusions from the existing studies on IFRS adoption and value relevance were characterized by conflicting results and mixed findings. This study attempts to evaluate the impact of adoption of International Financial Reporting Standards (IFRS) on the value relevance of financial information of Nigerian Deposit Money Banks. A mixed research approach was adopted for this study. To analyze the secondary data correlational research design was employed using Edward, Bells and Olhson (EBO) model. Primary data through structured questionnaire administered on a sample of 200 randomly selected preparers and users of banks financial statements was also used to provide alternative evidence. Data were analyzed using descriptive and econometric approaches. General least square (GLS) multiple regression analyses were employed to analyze the panel data based on random effect model using SPSS 17 statistical tool.The results from data analysis showed r calculated of 0.69 indicating a significant relationship between adoption of IFRS variables and value relevance indexes in the NDMBs, from the analysis of questionnaire responses. The relationship, using EBO model, between the variables used for post IFRS adoption analysis shows that share price (SP) is positively correlated with earning per share (EPS), change in earnings per share (CEPS) and book value per share (BVPS) at 0.368, 0.096 and 0.103 respectively meaning that SP and EPS have higher positive relationship but lower with CEPS and BVPS. Invariably, higher earnings attract higher SP which automatically enhances the confidence of investors in the financial statements after the adoption. The pre-IFRS R-squared is 0.35 while post-IFRS R-squared is 0.16 showing that post IFRS financial information has a weak value relevance. However, the elements that made up financial information are not value relevant in post IFRS adoption thereby giving a low cumulative relationship to share price. The study suggests concerted efforts by banks to strengthen the value relevance and improve users’ confidence of their financial reports since IFRS adoption has been made mandatory.